Kane, Pereboom, and Event-Causal Libertarianism. - Lemos, John (Philosophia, 2020)
This paper provides a brief review of some of the central elements of Robert Kane's event-causal libertarian theory of free will. It then goes on to consider four of the central criticisms Derk Pereboom has made of Kane's view and it shows how each of these criticisms can be reasonably answered. These criticisms are the no further power/control objection, the disappearing agent/luck objection, the randomizing manipulator objection, and the problem of responsibility for efforts of will.